Intention to Use Halal-Certified Bakery Ingredients among Online Muslims Entrepreneurs: Application of Extended Theory of Planned Behaviour (TPB) Model - Rosi Hasna Sari; Ahmad, Anis Najiha; Beta Kartika (Halalsphere, 2022)
The development of halal food industries has created more business opportunities for Muslim entrepreneurs. These Muslim entrepreneurs must ensure that only halal ingredients are used in their food products. Although there is a growing literature on halal management and consumerism, empirical studies on certified bakery ingredients and online entrepreneurs are limited. To fill this gap, factors influencing the intention to use halal-certified bakery ingredients among online entrepreneurs are being investigated. The data was obtained from 165 online Muslim entrepreneurs in Malaysia using convenience sampling. The adopted questionnaire was used as a research instrument, grounded by the extended Theory of Planned Behavior (TPB). The TPB model was extended in this study by including additional components to measure self-identity, moral obligation, and barriers. The results obtained based on the path analysis showed that the attitude and subjective norm of the entrepreneurs are both statistically significant in influencing the intention to use halal-certified bakery ingredients. In contrast, entrepreneurs’ perceived behaviour control, self-identity, and moral obligations had no significant influence on the intention to use halal-certified bakery ingredients